The elections of the great recession in Portugal: performance voting under a blurred responsability for the economy - Magalhães, Pedro (2015)
Reprinted from "Pedro C. Magalhães (2014). The Elections of the Great Recession in Portugal: Performance Voting under a Blurred Responsibility for the Economy, Journal of Elections, Public Opinion and Parties, 24:2, 125-133, DOI: 10.1080/17457289.2013.874352